Efficient optical modulation in ring structure based on Silicon-ITO heterojunction with low voltage and high extinction ratio - Rajput, Swati (2023)
We numerically propose a low voltage, high extinction ratio optical modulator with a tunable group delay in a resonance enhanced ring resonator based on Silicon (Si) - Indium Tin Oxide (ITO) heterojunction. This is accomplished by incorporating a thin ITO layer into a Si-ring resonator. By electrically inducing carrier changes in ITO, the epsilon-near-zero (ENZ) state of ITO is attained, resulting in a sudden change in optical absorption. The resonance condition shifts because of the ENZ state, and the transmission at the ring resonator's through port changes dramatically. The extinction ratio (ER) of 11 dB at a low forward bias of 1 V is reported with a low energy consumption of 2.6 fJ. An optical network has a non-trivial demand for a high extinction ratio optical modulator that operates at a low driving voltage and consumes minimal energy. The proposed ring modulator with a high extinction ratio at low driving voltage outperforms conventional waveguide-based modulators in terms of energy efficiency. In addition, we report around 25 psec of electrical tuning in the group delay The current concept has favorable results in terms of exploring tunable delay lines in conjunction with optical modulation with a high extinction ratio.